Relación causa-efecto de la publicidad televisiva de “ROQ” en la ciudad de Quevedo, año 2012 - Piuri Álvarez, Cristian Manuel (2012)
In Quevedo Canton, Province of Los Ríos, is conducting research that will lead to determine the cause and effect of television advertising "ROQ" in the city of Quevedo, period 2012. Is there much competition this Canton in this area, the reasons are many, the technology that pervades everywhere, social networks and media, are currently widely used means for entrepreneurs or traders of this Canton advertising theme with technology existing is much more varied and that social networks offer the opportunity to provide a service or product by this means and what is best without having to pay for the service. In some media there are fewer profits, and the causes are many, and is often not consulted viewers about the tastes and preferences that would require time to look at advertising, it is common to see people when in a television advertising appears simply change the channel while passing such advertising, but this is something that the viewer brings to prefer another channel that does not offer much publicity that is most striking and so does not become boring for the viewer. The aim of this study was to determine the cause and effect of television advertising "ROQ. The ad carries the desire to make profits for the company whose earnings are determined by the amount of advertising done, this is due to implement strategies and service quality, innovation and creativity all these in order to meet the needs of the employer which uses through advertising to sell their products or services and that these have the recognition of people. To study mechanisms which are needed to attract viewers and entrepreneur and so they request the service. All this will take some time, but time will not be wasted because it will lead us to many gains, which in a short time will be displayed.